Leader / Muhammad Asri Azuddin - Azuddin, Muhammad Asri (2023)
A person who leads a group, community, organisation, or even a country is called a leader. The artist took a satirical joke and turned it into a photograph to create this masterpiece. This piece was inspired by the political instability in Malaysia between 2020 and 2022, when the Prime Minister was replaced three times in a short amount of time. Party hopping shows how immature each leader is because they care more about their own position; even though they say they are trying to save the country (Yusainy, 2022). This kind of political behaviour is bad for everyone and should stop.